Building Bridges: Contemporary Perspectives on Gender, Sexuality and International Human Rights Law (2024)
This book includes a collection of essays authored by academics, activists, and practitioners reflecting on critical advances and challenges in the areas of gender and sexuality and their linkages to international law and human rights. Feminists have long intervened to advance women’s rights, substantial equality, and the eradication of gender-based violence using international law as an important tool, through policy action and the litigation of cases before the universal and regional human rights systems and other strategies. The LGBTIQ+ community has also injected a queer perspective to international law. Therefore, a diversity of scholars and activists discuss in this volume paramount issues in international law and explore them with a feminist, queer or gendered, and human rights perspectives. The essays promote a rich discussion of critical topics such as those connected to intersectional discrimination, violence against women and LGBTIQ+ persons, sexual and reproductive rights, and challenges to protect human rights in situations of armed conflict and contexts of crisis.